Model test of clogging effects on composite foundation of geosynthetic-encased steel slag column. Issue 5 (October 2022) - Liu, Kaiwen; Qiu, Ruizhe; Yan, Tengfei; Wu, Bowen; Fan, Jiying; Yue, Fei; Mei, Guoxiong
Abstract: Experiments were conducted to study the performance of geosynthetic encased steel slag column with a diameter of 150 mm and a length of 900 mm in a soft clay foundation. The effect of clogging was simulated by mixing the slag with 10% and 20% fines. The measured bearing capacity of the column treated foundation is notably increased to about 10 times than that of the untreated foundation, and is seldom affected by the intrusion of fines. The vertical stress within the soil at column tip attenuates to 85% and 60% of the stress close to the ground surface for the column with no fines and 20% fines, respectively. For the cases with fines content of 10% and 20%, the maximum excess pore pressure is in average 5% and 10% greater than the case without fines, respectively, and the dissipation rate of excess pore pressure is in average 18% and 24% slower than the case without fines. The column treated foundation prevents the water ponding on the surface as that occurs for the untreated foundation. The undrained shear strength of the soil close to the column increases by 18% at the depth of 100 mm, and 6% at the depth of half column, regardless of the fines. Highlights: Investigate the effect of clogging on the bearing capacity of the geosynthetic encased column. Study the distributions of the soil stress around the column and the excess pore pressure within the soil. Explore the improvement of the shear strength within the soil.